Peran Dinas Pemberdayaan Masyarakat Dan Kampung Dalam Permohonan Pemekaran Dusun Sarsangg Distrik Tanah Miring - Pohan, Farida Romaito; Yulia Ningrum, Nur Rohmah; Bangkit Wibowo, Juventus (Jurnal Administrasi Karya Dharma, 2024)
The Unitary State of the Republic of Indonesia is divided into provinces, which are further divided into districts and cities, according to Article 18 of the 1945 Constitution. Each province, district, and city have a regional administration that is governed by law. extend an invitation. The governments of provinces, regencies, and cities control and oversee their own activities in accordance with their powers of autonomy and assistance. The purpose of this study is to ascertain the Community and Village Empowerment Service's involvement in the Tanah Miring District's application for Sarsangg Hamlet enlargement. This study employed a descriptive approach using qualitative methodologies. Interviews, observation, and documentation were employed in the data collection process. According to this study, the Merauke Regency has been contacted by the Yasa Mulya Village authority.